PENGARUH PENINGKATAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI KOTA SIBOLGA - Harry Kurniadi Atmaja; Kasyful Mahalli (Ekonomi dan Keuangan, 2015)
The problem in this research is for finding out the influence of increasing the infrastructure of road, water, electricity, telephone over the economic growth in Sibolga City and also for understanding the recent overview of the condition of infrastructure in Sibolga City. This data uses time series which the period from 1989 up to 2013 in Sibolga City. The end of the result of four independent variables (roads, water, electricity, and telephone) has a variable that is gives a positive influence which it has a significant and positive effect over the growth of economic, that is water. While the other two variables road and phone don’t have a significant effect, but it has a positive effect over the growth of economic in Sibolga City, while one more variable that electricity does not have a significant and negative effect over the economic growth in Sibolga City.Keywords: Sibolga City, Infrastructure, Economic Growth.